(untitled) - Perreault, William D. (Boston, MA., 2006)
Essentials of Marketing is a brief version of Basic Marketing, the worldwide market leading Principles text. Basic Marketing and Essentials of Marketing are the first books to develop and present the 4Ps framework (Product, Price, Place, Promotion) which describes the components of the marketing mix and forms the foundation of Marketing. Like Basic Marketing, Essentials of Marketing offers a very thorough integration of the latest marketing themes, topics, and examples woven throughout. While Essentials of Marketing is a brief text, it is not a cut-and-paste of Basic Marketing. It is written carefully, thoroughly and specifically to be suitable for shorter Marketing courses. Author Bill Perreault shows this same dedication to the supplements package. Where most principles of marketing texts have separate supplement authors, Bill Perreault creates every item in the package. This unique involvement ensures quality, accuracy, and reliability.
Keywords: Marketing